Towards measuring the capacity utilization of gillnet vessels in Peninsular Malaysia. - Alam, Md. Ferdous; Mohd Noh, Kusairi; Tai, Shzee Yevr; Md. Nurul Islam, Gazi; Mohd Noh, Aswani Farhana
Resource dwindling in capture fisheries is a common problem irrespective of developed and developing country. This study addressed the capacity utilization and excess capacity problem in marine fisheries of Peninsular Malaysia. Primary data from 22 gillnet vessel operators from the states of Pahang and Perak were used in the study. Data Envelopment Analysis (DEA) models were formulated to estimate capacity output and capacity utilization. The parameters of the DEA models were estimated using General Algebraic Modelling System (GAMS). Average observed capacity utilization was 83% and 79% for Pahang and Perak vessels while the unbiased capacity utilization was 93% and 94% respectively. Excess capacity exists in the fisheries as the observed output is lower than those of the capacity outputs. The average technical efficiency of the gillnetters was 84%. Fifty percent of the vessels were fully technically efficient. The outputs could have increased by 37% and 26% if the vessels were operating at full capacity and at full technical efficiency. Average crew utilization ratio was optimal. However, energy use and fishing days-at-sea were greater than 1.00 indicating that vessels were operating with shortage of these inputs. The study indicates that excess capacity can be eliminated by withdrawing some vessels.